SOLID-PSEUDOPAPILLAR NEOPLASM OF THE PANCREAS IN A YOUNG WOMAN: A CLINICAL CASE - A. P. Koshel; S. S. Klokov; K. M. Popov; S. V. Vtorushin; M. V. Zavyalova; I. V. Stepanov; T. V. Dibina; E. B. Mironova; E. S. Drozdov (Сибирский онкологический журнал)
Treatment outcomes of soloid-pseudopapillar tumor of the pancreas in a young woman have been presented. Soloid-pseudopapillar tumor of the pancreas is a rare neoplasm. As a rule, it is detected by chance during routine screening US examinations. Diagnosis is frequently delayed and tumor size at presentation is frequently large. In case of systic pancreatic lesion, soloid-pseudopapillar tumor should be considered in the diagnosis. As a low-grade malignancy, the tumor seldom recurs and metastasizes.